Treatment of Single or Multiple Brain Metastases by Hypofractionated Stereotactic Radiotherapy Using Helical Tomotherapy - Nagai, Aiko (Molecular Diversity Preservation International (MDPI), 2014)
This study investigated the clinical outcomes of a 4-fraction stereotactic radiotherapy (SRT) study using helical tomotherapy for brain metastases. Between August 2009 and June 2013, 54 patients with a total of 128 brain metastases underwent SRT using tomotherapy. A total dose of 28 or 28.8 Gy at 80% isodose was administered in 4 fractions for all tumors. The mean gross tumor volume (GTV) was 1.9 cc. Local control (LC) rates at 6, 12, and 18 months were 96%, 91%, and 88%, respectively. The 12-month LC rates for tumors with GTV ≤0.25, >0.25 and ≤1, and >1 cc were 98%, 82%, and 93%, respectively; the rates were 92% for tumors >3 cc and 100% for >10 cc. The 6-month rates for freedom from distant brain failure were 57%, 71%, and 55% for patients with 1, 2, and ≥3 brain metastases, respectively. No differences were significant. No major complications were observed. The 4-fraction SRT protocol provided excellent tumor control with minimal toxicity. Distant brain failure was not so frequent, even in patients with multiple tumors. The results of the current study warrant a prospective randomized study comparing single-fraction stereotactic radiosurgery (SRS) with SRT in this patient population.